A clandestine in the flora of Brazil: Commelina clandestina (Commelinaceae) - Hassemer, Gustavo (Phytotaxa, 2017)
Commelina clandestina has been for a long time a problematic citation for the flora of Brazil. Here, I clarify the original publication and authorship of C. clandestina Mart. and C. clandestina Hort.Berol. ex Kunth, designate lectotypes for these names, propose their synonymisation with C. tuberosa, and argue that the seeds from which the type specimens were grown in Munich and Berlin did not originate from Brazil. Finally, to summarise recent advances to the taxonomic knowledge of Commelina, I provide here an updated identification key for the genus in Brazil.